Responding to Emerging Diseases Requires Multi-disciplinary and One Health Training, Egypt - Amira Roess; Sally Lahm; Ibrahim Kabbash; Amal Saad-Hussein; Ashraf Shaalan; Ossama Rasslan; Mohamed Mohamed (Ubiquity Press, 2018)
Background: In Egypt, several infectious diseases of zoonotic origin have emerged in recent years like H1N1, MERSCoV and H5N1, the latter now endemic. Responding to these diseases requires a workforce trained in multi-disciplinary approaches to zoonotic disease research and control. It is difficult to deliver multidisciplinary and one health training globally because of the limited number of higher education programs that support such training. In low and middle-income countries where the impacts of emerging zoonotic diseases are felt more directly there is enthusiasm for such training and the use of e-technology can foster international, long-term collaborations. Objectives: To provide health training for infectious diseases research and to foster multidisciplinary collaboration. Methods: We designed and simultaneously held two training workshops, one focused on pediatric infectious diseases and another on emerging infectious diseases to meet the objective. Both workshops had pre- and post-workshop activities for multi-disciplinary methods with an emphasis on the use of mobile technologies to enhance emerging infectious diseases surveillance and research for public health professionals in Egypt. Faculty and scientists from all universities in Egypt and from the National Research Center were invited to participate. Results: 85 participants attended, 31 abstracts were submitted, and over a 3 year period 3 international grant applications were submitted, and 4 abstracts were presented at international conferences. An online forum was developed to continue building collaboration. Conclusions: Interactive on-site workshops are suitable for providing multi-disciplinary training for disease surveillance, research and disease control. Participants shared the opinion that grant proposal and scientific manuscript writing were important skills that they felt they did not have. Long term investments in workshops of this nature are needed to build upon the excitement generated by these activities.